PENGARUH VARIABLE DARK TOURISM TERHADAP KEPUASAN WISATAWAN BERKUNJUNG DI BUKITTINGGI (STUDI KASUS LOBANG JEPANG) - Mahrida, Juniar; Afrilian, Pepy (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2024)
The main problem in this research is whether there is an influence of dark experience, engaging entertainment, unique learning experience, and casual interest on tourist satisfaction (case study of dark tourism Lubang Japang Bukittinggi). The aim of this research is to find out whether there is an influence of dark experience, engaging entertainment, unique learning experience, and casual interest on tourist satisfaction (case study of dark tourism Lubang Japang Bukittinggi). The method used in this research is quantitative. Data collection techniques involved administering questionnaires and selecting respondents through incidental sampling, resulting in a total of one hundred respondents determined using the Slovin formula. The data analysis techniques used are validity test, reliability test, multiple linear, regression analysis, partial t test, simultaneous f test, and coefficient of determination test.Based on research results from distribution of questionnaires to 100 respondents, it snow that the engaging entertainment and unique learning experience variables have asignificant influence on tourist satisdaction. However, the dark experience and casual interset variables have no influence. And the simultaneous f test results of the variables dark expperience, engaging entertainment, unique learning experience, and casual interst have a significant influence simultaneously on tourist decision variables.